2021
DOI: 10.1002/uog.23665
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic artery Doppler in prediction of pre‐eclampsia: insights from hemodynamic considerations

Abstract: Linked article: This Correspondence comments on Sapantzoglou et al. and Sarno et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…In women that developed PE, the ophthalmic artery PSV ratio was increased compared with unaffected cases, and the degree of the increase was associated inversely with gestational age at delivery with PE. We found that there was a small increase in PSV1 in PE compared with unaffected cases, possibly reflecting a small increase in cardiac output, and a considerably greater increase in PSV2, suggesting that the high PSV ratio is mainly due to increased peripheral vascular resistance 17,18 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In women that developed PE, the ophthalmic artery PSV ratio was increased compared with unaffected cases, and the degree of the increase was associated inversely with gestational age at delivery with PE. We found that there was a small increase in PSV1 in PE compared with unaffected cases, possibly reflecting a small increase in cardiac output, and a considerably greater increase in PSV2, suggesting that the high PSV ratio is mainly due to increased peripheral vascular resistance 17,18 .…”
Section: Discussionmentioning
confidence: 65%
“…The first systolic wave (PSV1) is created by cardiac systole, with the opening of the aortic valve and ejection of blood into the aorta, whilst the second systolic wave (PSV2) is a reflective wave formed by the systolic pulse wave reaching smaller, higher-resistance arterioles and being reflected back towards the heart. At the level of the aortic arch, a fraction is diverted cranially to the cerebral circulation as a forward wave to create PSV2 17,18 . In this way, PSV2 is most influenced by peripheral arterial compliance and resistance, whilst PSV1 is more affected by cardiac output.…”
Section: Introductionmentioning
confidence: 99%
“…The PSV ratio is the interplay between PSV1 and PSV2. PSV1 is created by cardiac systole, generating a rapid upstroke to reach systolic peak pressure 27 , whereas, PSV2 is created by reflection of the systolic wave as it encounters the higher resistance of smaller arterioles 28 . Specifically, the wave is reflected back towards the aortic arch, where a fraction is diverted cranially to the cerebral circulation as a forward wave, to create the second systolic peak (PSV2) 28 .…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Effect on cerebral arteries. At the level of the aortic arch, a fraction of the RW turns cranially and continues as a forward wave to generate a second systolic velocity peak (P2) in the cerebral arteries [1][2][3] and, in particular, in the OA 14 , if reflection is strong enough. The amplitude of P2 is related to the intensity of the RW, and OA-PR might serve as a relative measure of the reflection intensity.…”
Section: Impact Of Pulsed-wave Reflection On Ophthalmic Artery Dopple...mentioning
confidence: 99%